2023
DOI: 10.1111/acel.14020
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the redox system for cardiovascular regeneration in aging

Meret Sarah Allemann,
Pratintip Lee,
Jürg H. Beer
et al.

Abstract: Cardiovascular aging presents a formidable challenge, as the aging process can lead to reduced cardiac function and heightened susceptibility to cardiovascular diseases. Consequently, there is an escalating, unmet medical need for innovative and effective cardiovascular regeneration strategies aimed at restoring and rejuvenating aging cardiovascular tissues. Altered redox homeostasis and the accumulation of oxidative damage play a pivotal role in detrimental changes to stem cell function and cellular senescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 244 publications
(392 reference statements)
2
4
0
Order By: Relevance
“…Our findings also confirmed that PAA induces morphological and metabolic changes in aortic ECs that lead to cellular senescence and consequently impairment of angiogenesis. Corroborating these results, our and others’ previous studies demonstrated that accumulation of senescent ECs plays a causative role in pathogenesis of vascular diseases such as atherosclerosis 1,33 . Therefore, the gut-derived PAA can be potentially suggested as a key determinant in the induction of endothelial senescence and the development of atherosclerosis upon aging.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings also confirmed that PAA induces morphological and metabolic changes in aortic ECs that lead to cellular senescence and consequently impairment of angiogenesis. Corroborating these results, our and others’ previous studies demonstrated that accumulation of senescent ECs plays a causative role in pathogenesis of vascular diseases such as atherosclerosis 1,33 . Therefore, the gut-derived PAA can be potentially suggested as a key determinant in the induction of endothelial senescence and the development of atherosclerosis upon aging.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings showed that AQP1 is essential for HDAC4 phosphorylation at Serine site 632, which subsequently controls its nuclear export, in proliferating ECs. It returns to the fact that redox/metabolic status in ECs orchestrates permanent changes in their epigenetic programming [2]. The CaMKII-mediated hierarchical phosphorylation of HDAC4 S632 facilitates its subcellular localization [22].…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that endothelial cells undergo permanent alterations in their metabolic and redox states during aging [2,6]. The stable ROS, H 2 O 2 , at higher concentrations, alters mitochondrial dynamics, impairs respiratory chain activity, and disrupts redox homeostasis [2].…”
Section: Aqp1 Differentially Orchestrates Endothelial Energy Supply A...mentioning
confidence: 99%
See 2 more Smart Citations